Surrealism key concepts - Fijalkowski, Krzysztof; Richardson, Michael (Milton Park, Abingdon, Oxon Routledge, Taylor & Francis Group, 2016)
Emerging from the disruption of the First World War, surrealism confronted the resulting 'crisis of consciousness' in a way that was arguably more profound than any other cultural movement of the time. The past few decades have seen an expansion of interest in surrealist writers, whose contribution to the history of ideas in the twentieth-century is only now being recognised. Surrealism: Key Concepts is the first book in English to present an overview of surrealism through the central ideas motivating the popular movement. An international team of contributors provide an accessible examination of the key concepts, emphasising their relevance to current debates in social and cultural theory.
Part I: Contexts: 1. Heraclitus, Hegel and dialectical understanding / Jonathan P. Eburne -- 2. Hermeticism and the magical tradition / Guy Girard -- 3. Freudian Origins / Jean-Michel Rabatâe -- 4. Utopia: the Revolution in Question / Georges Sebbag -- 5. Sade and revolutionary violence / Michael Richardson -- 6.'The Speaking Flame': the Romantic Connection / Michael Lèowy -- 7. Dada / Krzysztof Fijalkowski. -- Part 2: Key concepts: 8.Community at Play / Raymond Spiteri -- 9. Otherness and Self-Identity / Michael Richardson -- 10. Poetics / Michael Richardson -- 11. Objective Chance / Raihan Kadri, Michael Richardson and Krzysztof Fijalkowski -- 12. The Chance Encounter: Language and Madness / Michael Stone-Richards -- 13. Dream: a Manifesto of the Manifest Dream / Georges Sebbag -- 14. Mad Love / Dawn Ades and Michael Richardson -- 15. Convulsive Beauty / Krzysztof Fijalkowski -- 16. The Object / Krzysztof Fijalkowski -- 17. Black Humour / Michael Richardson -- 18. The Ecological Imperative / Donna Roberts -- 19. Magic Art / Bertrand Schmitt -- 20. The Marvellous / Joyce Suechun Cheng and Michael Richardson -- 21. The Supreme Point / Krzysztof Fijalkowski and Michael Richardson -- Chronology of Surrealism -- Bibliography -- Index.
Includes bibliographical references (pages 267-278) and index.
Keywords: Surrealism